Structural Investigations of Glass Ceramics in the Ga2S3-GeS2-CsCl System - Ledemi, Yannick; Bureau, Bruno; Calvez, Laurent; Le Floch, Marie; Roze, Mathieu; Lin, Changgui; Zhang, Xiang H.; Allix, Mathieu; Matzen, Guy; Messaddeq, Younes [UNESP] (Amer Chemical Soc, 2009)
Transparent glass ceramics have been prepared in the Ga2S3-GeS2-CsCI pseudoternary system appropriate heat treatment time and temperature. In situ X-ray diffraction at the heat treatment temperature and Cs-133 and Ga-71 solid-state nuclear magnetic resonance have been performed in function of annealing time to understand the crystallization process. Both techniques have evidenced the nucleating agent role played by gallium with the formation of Ga2S3 nanocrystals. on the other hand, cesium is incorporated very much later into the crystallites during the ceramization. Moreover, the addition of CsCl, which is readily integrated into the glassy network, permits us to shift the optical band gap toward shorter wavelength. Thus, new glass ceramics transmitting in the whole visible range up to 11.5 mu m have been Successfully synthesized from the (Ga2S3)(35)-(GeS2)(25)-CsCl40 base glass composition.